The impacts of market size and data-driven marketing on the sales mode selection in an Internet platform based supply chain - Liu, Weihua; Yan, Xiaoyu; Li, Xiang; Wei, Wanying (Transportation research. Part E, Logistics and transportation review, 2020)
•Agency selling mode and reselling mode of the platform are investigated.•The impacts of data-driven marketing (DDM) on the sales mode selection are studied.•The platform prefers agency selling mode only when the market size is moderate.•With an increase in DDM efficiency, the platform more prefers the reselling mode.•The sales mode with higher sales volume is not more profitable in some conditions. This study investigates a platform’s preferences between agency selling and reselling considering the impact of data-driven marketing (DDM). Four models are built: No-DDM+agency selling, No-DDM+reselling, DDM+agency selling, DDM+reselling. Sales volumes, profits and profit growth rates in different sales modes are compared. Results show that with an increase in DDM efficiency, the platform is more willing to adopt the reselling mode. In addition, without DDM, the sales mode with higher sales volume is not more profitable within a certain market size. DDM can help avoid this phenomenon to a certain extent.